Pembuatan Aplikasi Kegiatan Warga Pada RT 06 RW 06 Kelurahan Airlangga Berbasis Android - Arya Nugraha; Agustinus Noertjahyana; Lily Puspa Dewi (Jurnal Infra, 2018)
The use of smartphone technology to obtain or disseminate information in various activities of citizens is very rarely used. RT managers usually use the correspondence to give news of their citizens if they want to hold an event in their neighborhood. Letters distributed to residents, usually only in the form of agenda, place and time of implementation. Not infrequently, residents who receive letters long-time terebut forget the agenda that has been planned by the RT management. Due to a written letter that is only informative and not as a media reminders / reminder of the event.The process of making this program is equipped with Java and PHP as programming languages, MySQL as database, Android Studio and Sublime which is used to display the source code of programming language and web browser as media to display website which have been made in Sublime.The results obtained from the applications that have been made, among others, the making of citizen activities and citizens' appeal made by the chairman of the household, monthly financial reports made by the treasurer, and opinions of citizens who can be used to share opinions among all citizens. And also the notification and alarm activities to facilitate interaction among fellow citizens.